From Risk Communication to Collective Action: The Role of Social Media Influencers in Building Social Cohesion and Community Resilience in Indonesia (Universitas Terbuka, 2025)
This paper explores the emerging role of social media influencers in disaster risk communication and community resilience in Indonesia. Through a literature review of academic journals, e-books, reports, and secondary sources published over the last decade, the study synthesizes insights on how influencers shape public understanding, foster social cohesion, and mobilize collective action in times of crisis. The findings highlight three interrelated roles. First, influencers act as amplifiers of risk information, extending the reach and accessibility of disaster messages beyond institutional channels, though risks of misinformation remain significant. Second, they cultivate social cohesion and community identity by leveraging parasocial trust and cultural values such as gotong royong, reframing disasters as collective struggles that demand solidarity. Third, influencers facilitate activism and resource mobilization, transforming digital attention into donations, volunteering, and grassroots engagement, albeit often in episodic or performative ways. The review emphasizes both opportunities and challenges: while influencers democratize access and enhance engagement, their contributions may exclude marginalized groups and risk eroding trust when authenticity is questioned. The paper argues that hybrid communication models—linking influencers with government agencies, NGOs, and local communities—offer the most promising pathway for building inclusive resilience. The study contributes to the literature on digital risk communication, social cohesion, and civic activism while offering practical recommendations for integrating influencer engagement into disaster preparedness and response strategies in Indonesia.